2021
DOI: 10.1111/deci.12549
|View full text |Cite
|
Sign up to set email alerts
|

Using forecasting to evaluate the impact of COVID‐19 on passenger air transport demand

Abstract: The COVID‐19 pandemic caused a drastic drop in passenger air transport demand due to two forces: supply restriction and demand depression. In order for airlines to recover, the key is to identify which force they are fighting against. We propose a method for separating the two forces of COVID‐19 and evaluating the respective impact on demand. Our method involves dividing passengers into different segments based on passenger characteristics, simulating different scenarios, and predicting demand for each passeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…To be specific, Li et al. (2021) analyze the potential influence of COVID‐19 on passenger air transport demand and make forecasts under different cases by using simulation. Their results reveal that the two forces (i.e., supply restriction and demand depression) will have opposite impacts on air transport demand concerning different passenger segments.…”
Section: Demand Side Risk Under Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…To be specific, Li et al. (2021) analyze the potential influence of COVID‐19 on passenger air transport demand and make forecasts under different cases by using simulation. Their results reveal that the two forces (i.e., supply restriction and demand depression) will have opposite impacts on air transport demand concerning different passenger segments.…”
Section: Demand Side Risk Under Pandemicmentioning
confidence: 99%
“…Li et al. (2021) and Shen & Sun (2021) examine the huge uncertainty of demand under the COVID‐19 pandemic and make efforts to address it for supply chain resilience. To be specific, Li et al.…”
Section: Demand Side Risk Under Pandemicmentioning
confidence: 99%
“…In their paper entitled “Using forecasting to evaluate the impact of COVID‐19 on passenger air transport demand,” Li et al. (2023) studied the impact of the COVID‐19 pandemic on passenger air transport by proposing a forecasting approach to separate the supply restriction and demand depression arising from the COVID‐19 pandemic, and subsequently evaluated the impact of each force on the passenger air transport demand. Their method includes four steps: passenger segmentation (based on predefined groups), forecasting model selection (SARIMA), scenario simulation (business as usual versus the pandemic scenario), and prediction comparison.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also showed that the impacts of demand depression and supply restriction were heterogeneous based on passenger segments (nine segments based on age group and purpose of the trip). Finally, they offered two strategies depending on passenger segments: (1) resume flights and (2) restore passenger confidence/increase passenger willingness to fly (Li et al., 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the fourth study, Dube et al (2021) speci ed that because of air travel is in full swing, general problems will not resolve right away. He proposed to aviation specialists that safeguarding passengers' health and safety, planning ticket prices, boosting e ciency, ensuring high-quality in-ight amenities, and maintaining such safeguards is likewise essential for the development of air tra c. In the fth study, Li et al (2021) speci ed that there was a sharp drop in passenger air travel because of the COVID-19 for two reasons. These are the breakdown of demand and supply of restrictions.…”
Section: Literature Reviewmentioning
confidence: 99%